Micro : a novel - Crichton, Michael, 1942-2008.; Preston, Richard, 1954- (New York : Harper, 2011)
7 graduate students from Cambridge travel to Hawaii, where they are miniaturized by an evil entrepreneur. They escape to the rain forest where, only six inches tall, they do battle with insects.
Map on lining papers.
Includes bibliographical references (p. [425]-429).
Keywords: Microbiologists -- Fiction; Nanotechnology -- Fiction; Oahu (Hawaii) -- Fiction; Suspense fiction